The organic chemistry behind the recycling of poly(bisphenol-A carbonate) for the preparation of chemical precursors: A review - Gilbert, Elangeni Ana (2022)
Production and consumption of poly(bisphenol-A carbonate) resins are seeing a worldwide increase. However, their usage lifetimes are short and their final disposition as landfills pose environmental and health risks, due to the release of toxic bisphenol-A (BPA). The development of alternative recycling routes is thus becoming subject of increasing interest. In this review, the main recycling processes of poly(bisphenol-A carbonate) are described and critically compared, with special focus on the chemical mechanisms. While mechanical recycling is possible, the end products are restricted only to polymer blends, whose main mechanical properties decrease with each compounding cycle. In turn, chemical recycling can produce BPA monomer and a variety of by-products that can be used in different industries, including the polymeric field, as synthesis reagents and precursors. The operation conditions of each method are reviewed, as well as the different results obtained in terms of product yield, composition, selectivity and reaction times. Reaction mechanisms are described in detail and a view on the usability of each end product is offered.